The Role of Teachers in Shaping Students' Character of Appreciating Achievement and Social Care Based on the Dasa Paramita - Heri Heri; Sutrisno Sutrisno; Sulan Sulan (Jurnal Mamangan, 2023)
Character education is an urgent need in the midst of the moral challenges faced by today’s younger generation. The Maitreya Buddhist Sunday School (SMB) in Batam, as a non-formal educational institution, aims to instill noble values from an early age, especially among junior and senior high school students. This research focuses on three main questions: how teachers act as role models, character builders, and motivators in cultivating the values of appreciating achievement and social care based on the Dasa Paramita; which Dasa Paramita values are most relevant and dominant in shaping these character traits; and how the teachers’ role impacts students’ behavior and habits in the SMB Maitreya Batam environment. A qualitative approach with a case study design was used. Data were collected through observation, in-depth interviews, and focus group discussions with teachers, students, parents, and school administrators. Thematic analysis was applied through coding, categorization, and interpretation to gain a deep understanding of the teachers’ role and the implementation of Dasa Paramita values in learning and character building. The results show that teachers at SMB Maitreya Batam play a key role as role models, character builders, and motivators in instilling Dasa Paramita values, especially the character of appreciating achievement and social care. The most dominant values for appreciating achievement are effort (vīriya), wisdom (paññā), and determination (adhiṭṭhāna), while for social care they are generosity (dāna), morality (sīla), and loving-kindness (mettā), supported by integrative values such as patience (khanti) and skillful means (upāya). These values not only strengthen academic achievement but also build balanced social character, making students more open, disciplined, empathetic, and caring toward their environment. The findings confirm the relevance of the Dasa Paramita as an effective moral foundation for character education in a non-formal Buddhist setting.